KETERKAITAN ANTARA PERIKLANAN SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN GENERASI Z - Ramah Sri Wulandari; Muhamad Yusuf; Ade Kurniawan; Safitri Putri Derajat (Desanta Publisher, 2025)
This study examines the effectiveness of social media advertising in capturing the attention of Generation Z. This generation has unique consumer characteristics, such as reliance on digital technology, a preference for online shopping, and trust in reviews and recommendations from other users. Social media platforms like Instagram, TikTok, and Facebook have become strategic tools due to their interactive nature and accessibility. Creative, relevant, and engaging advertising content has been proven to significantly influence purchasing decisions. Additionally, trust plays a key role in building loyalty, with elements such as quick responses, transparency, and consistent product quality being primary determinants. This study also highlights Generation Z's preference for personalized and value-driven shopping experiences. Therefore, advertisements emphasizing transparency, honesty, and interactivity have great potential to foster emotional connections with consumers, positioning social media as a critical tool in marketing strategies to enhance brand engagement and customer loyalty.